SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT SPAREPART PADA CV. PREMIERE WOOD MANUFACTURING DI SIDOARJO, JAWA TIMUR - Luluk Masluka; Soesilawati Soema Atmadja; Mochamad Fatchur Rohman (Ekomania, 2023)
This study aims to determine the credit sales accounting information system applied by CV. Premiere Wood Manufacturing and analyze whether the credit sales accounting information system is in accordance with the SOP (Standard Operating Procedure) applied by the company. The data used by the researcher is primary data, obtained from direct observation to the company and interviews with the sales department. The method used in this study uses a descriptive qualitative approach, which means that researchers identify problems with credit sales accounting information systems in CV. Premiere Wood Manufacturing.